Pengaruh Model Project Based Learning Dengan Alat Peraga Bokstik Terhadap Prestasi Belajar Matematika Siswa - Maulinda Nur Aisyah; Lilis M. Fitriyah; Nur Fitriyah Indraswari (UNIKA SANTU PAULUS RUTENG, 2020)
The aims of this study was to know whether there is influence of the project based learning model is BOKSTIK in statistic to learning achievements of mathematics of class VIII MTs Mambaul Hikmah academic year 2018/2019. The approach of this study is experimental quantitative with one group pretest posttest design. The instrument in this study are a pretest and posttest. The subject of this study is all students of class VIII MTs Mambaul Hikmah with samples of class VIII B amount to 30 student data analysis was permormed using the t-test. The results showed that then was rejected and was accepted with a significant level of 5%, and . Therefore the use of project based learning models with BOKSTIK in statistic has an effect on the mathematics learning achievement of class VIII MTs Mambaul Hikmah academic year 2018/2019